(untitled) (Discourse of Law and Administration, 2025)
Mankind’s dream of a ‘law ex machina’ dates back as far as the 17th century in Europe. In turn, the critique of this dream can also be traced back to the early 19th century. Today law and ethics are struggling to keep up with developments in information technology at the dawn of the digital age in the 21st century. This applies in particular to the impending milestone of moving from conventional information systems that merely reproduce data to a productive, learning algorithm of artificial intelligence. Its application in administration would raise entirely new fundamental questions about the predictability, rule of law and legitimacy of administrative action.